Empowering Educators: Leadership Strategies for Unlocking Teacher Potential in Madrasahs - Salwa Putri Verhan; Makmur Syukri (Al-Qalam Institue, 2026)
The purpose of this study is to examine the efforts of school leadership in enhancing teacher motivation through the implementation of the Unlock Your Potential strategy, including planning, implementing, and evaluating strategies for teacher development, as well as recognizing outstanding performance. This study employs a descriptive qualitative method, using observations, interviews, and document analysis with school leaders and teachers as participants. Data were analyzed through reduction, presentation, and drawing conclusions. The findings reveal that (1) efforts to increase teacher motivation involve personal approaches, guidance, support for learning facilities, and recognition of high-performing teachers; (2) strategies for teacher development are systematically implemented through training, workshops, ongoing coaching, academic supervision, and provision of supporting infrastructure; (3) supervision and evaluation are conducted periodically via monitoring, performance assessment, and evaluation meetings to improve competence and teaching quality; and (4) appreciation for teachers is given verbally or in writing to foster motivation and a positive work environment. The study implies that structured leadership strategies combined with recognition and supportive supervision can effectively enhance teacher motivation, competence, and overall educational quality.